Combined Deficiency of the Melanocortin 5 Receptor and Adenosine 2A Receptor Unexpectedly Provides Resistance to Autoimmune Disease in a CD8+ T Cell-Dependent Manner - McDonald, Trisha; Muhammad, Fauziyya; Peters, Kayleigh; Lee, Darren J. (Frontiers in Immunology, 2021)
Regulatory immunity that provides resistance to relapse emerges during resolution of experimental autoimmune uveitis (EAU). This post-EAU regulatory immunity requires a melanocortin 5 receptor (MC5r)-dependent suppressor antigen presenting cell (APC), as shown using a MC5r single knock-out mouse. The MC5r-dependent APC activates an adenosine 2A receptor (A2Ar)-dependent regulatory Treg cell, as shown using an A2Ar single knock-out mouse. Unexpectedly, when MC5r-/- post-EAU APC were used to activate A2Ar-/- post-EAU T cells the combination of cells significantly suppressed EAU, when transferred to EAU mice. In contrast, transfer of the reciprocal activation scheme did not suppress EAU. In order to explain this finding, MC5r-/-A2Ar-/- double knock-out (DKO) mice were bred. Naïve DKO mice had no differences in the APC populations, or inflammatory T cell subsets, but did have significantly more Treg cells. When we examined the number of CD4 and CD8 T cell subsets, we found significantly fewer CD8 T cells in the DKO mice compared to WT and both single knock-out mice. DKO mice also had significantly reduced EAU severity and accelerated resolution. In order to determine if the CD8 T cell deficiency contributed to the resistance to EAU in the DKO mice, we transferred naïve CD8 T cells from WT mice, that were immunized for EAU. Susceptibility to EAU was restored in DKO mice that received a CD8 T cell transfer. While the mechanism that contributed to the CD8 T cell deficiency in the DKO mice remains to be determined, these observations indicate an importance of CD8 T cells in the initiation of EAU. The involvement of CD4 and CD8 T cells suggests that both class I and class II antigen presentation can trigger an autoimmune response, suggesting a much wider range of antigens may trigger autoimmune disease.